RANCANG BANGUN SEPEDA LISTRIK DENGAN TENAGA SURYA SEBAGAI KENDARAAN ALTERNATIF DAN RAMAH LINGKUNGAN UNTUK MASYARAKAT - Muhammad Firman; M. Hasbi; Harizal Latif (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
The biggest problem faced by the countries in the world including Indonesia is the energy problem. Currently, Indonesia has experienced an energy crisis that is very alarming. Availability of Fuel of the Indonesian nation dwindling even have to import from other countries. The purpose of this study was to determine the mileage when not using solar power and determine the mileage when using solar power, the expenses needed for electric motorcycles using solar power. The study was conducted using the method of theoretical and experimental approaches to get the parameters-parameters. The object of research was done on electric bikes with solar power. The research design used in data collection and the materials used to solve the problem by conducting interviews, frequently asked questions directly related to the problem. Of the trial data obtained power generated electric bicycle without using solar power has an average value on a flat road is 14.5 km / h, the uphill road is 10.9 km / h. While electric bikes using solar power has the average value on a flat road is 17.7 km / h, the uphill road is 13.7 km / h. Economic aspects of the comparison of electric bicycles to use solar power with gasoline motors are able to save costs in one year is Rp 1,348,000,- In a modification of the electric motor in the electrical circuit required to try neat.